Предмет: Алгебра,
автор: hande1149
2у+1/у2+6у+9 у-2/у2+3у : у2+6/у3-9у=у-3/у+3. найти значение выражения Подробно!!!! Срочно!!!!
Ответы
Автор ответа:
0
Ответ:
(2у + 1/у^2 + 6у + 9 - у - 2/у^2 - 3у) - у^2 + 6/у^3 - 9у = 2у + 1/у^2 + 6у + 9 - у - 2/у^2 - 3у - у^2 + 6/у^3 - 9у = 8у + 1/у^2 + 9 - у - 2/у^2 - 3у - у^2 + 6/у^3 - 9у = 7у + 1/у^2 + 9 - 2/у^2 + 6/у^3 - 9у = - 2у - 1/у^2 + 9 + 6/у^3.
Объяснение:
Пойдёт?
Похожие вопросы
Предмет: Математика,
автор: sofiakosob
Предмет: Физика,
автор: kind559ship
Предмет: Биология,
автор: Аноним
Предмет: Математика,
автор: vodyaniikov1969
Предмет: Математика,
автор: альмира2222220